2019
DOI: 10.1002/prp2.551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monocyte chemoattractant protein‐1, macrophage inflammatory protein‐1α, and interferon‐α2a on P450 enzymes in human hepatocytes in vitro

Abstract: Some immunomodulatory agents stimulate the release of cytokines capable of suppressing P450 enzymes and potentially affecting pharmacokinetics of coadministered medications. Cytokines released in response to an immunomodulator in the blood ex vivo can be used to screen for the potential for drug‐drug interactions. Tilsotolimod, an investigational agonist of Toll‐like receptor 9, stimulated the release of macrophage chemoattractant protein‐1 (MCP‐1), macrophage inflammatory protein‐1α (MIP‐1α), and interferon‐α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The in vitro effect of IL‐6 on the mRNA expression of CYP enzymes in primary human hepatocytes have been reported in multiple studies 25‐43 . IL‐6 substantially downregulates the mRNA expression of CYP3A4 up to 100‐fold at 10 ng/mL, 26–28,30–32,34–43 whereas other CYP enzymes are downregulated 1.5‐ to 8‐fold by 10 ng/mL IL‐6 26–28,31,34,35,37–43 .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The in vitro effect of IL‐6 on the mRNA expression of CYP enzymes in primary human hepatocytes have been reported in multiple studies 25‐43 . IL‐6 substantially downregulates the mRNA expression of CYP3A4 up to 100‐fold at 10 ng/mL, 26–28,30–32,34–43 whereas other CYP enzymes are downregulated 1.5‐ to 8‐fold by 10 ng/mL IL‐6 26–28,31,34,35,37–43 .…”
Section: Resultsmentioning
confidence: 97%
“…The in vitro effect of IL-6 on the mRNA expression of CYP enzymes in primary human hepatocytes have been reported in multiple studies. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] IL-6 substantially downregulates the mRNA expression of CYP3A4 up to 100-fold at 10 ng/mL, [26][27][28][30][31][32][34][35][36][37][38][39][40][41][42][43] whereas other CYP enzymes are downregulated 1.5-to 8-fold by 10 ng/mL IL-6. [26][27][28]31,34,35,[37][38][39][40][41][42][43] A study reported a 2-fold upregulation of CYP2D6 mRNA by IL-6, 34 howe...…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, tilsotolimod increased CYP1A2 and CYP2B6 mRNA levels by 2- and 5-fold, respectively, at concentrations over 2.5 ng/ml, and reduced CYP2B6 enzyme activity by 46%. That study established that while INF-2α is inactivated in human liver cells, it mediates the effects of tilsotolimod on CYP1A2 and CYP2B6 expression ( Czerwiński et al, 2019 ).…”
Section: Introductionmentioning
confidence: 95%